2015
DOI: 10.1148/rg.2015140130
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Trauma: A Radiologist’s Guide to Imaging Trauma Patients Aged 65 Years and Older

Abstract: Radiologists play an important role in evaluation of geriatric trauma patients. Geriatric patients have injury patterns that differ markedly from those seen in younger adults and are susceptible to serious injury from minor trauma. The spectrum of trauma in geriatric patients includes head and spine injury, chest and rib trauma, blunt abdominal injury, pelvic fractures, and extremity fractures. Clinical evaluation of geriatric trauma patients is difficult because of overall frailty, comorbid illness, and medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 80 publications
0
19
1
2
Order By: Relevance
“…Indeed, recent guidelines have suggested more liberal imaging strategies in this population are appropriate. 27,28 The paradoxical observation of lower pretransfer imaging odds with higher severity of the worst injury (AIS) but lower severity of overall injuries (NISS) observed in our study may be explained by the fact that the indication to transfer is clearer with severe single-system injury than nonneurological multisystem trauma. The increased odds of pretransfer imaging in men could be explained by the greater suspicion of high-impact mechanisms 29 or of anticoagulant therapy 30 in men, despite adjustment for these factors.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Indeed, recent guidelines have suggested more liberal imaging strategies in this population are appropriate. 27,28 The paradoxical observation of lower pretransfer imaging odds with higher severity of the worst injury (AIS) but lower severity of overall injuries (NISS) observed in our study may be explained by the fact that the indication to transfer is clearer with severe single-system injury than nonneurological multisystem trauma. The increased odds of pretransfer imaging in men could be explained by the greater suspicion of high-impact mechanisms 29 or of anticoagulant therapy 30 in men, despite adjustment for these factors.…”
Section: Discussioncontrasting
confidence: 54%
“…The association with age may be explained by the greater presence of preexisting conditions and anticoagulant use in this population, the higher probability of severe injury even with low‐impact mechanisms, and the reduced lifetime impact of ionizing radiation in the elderly. Indeed, recent guidelines have suggested more liberal imaging strategies in this population are appropriate 27,28 . The paradoxical observation of lower pretransfer imaging odds with higher severity of the worst injury (AIS) but lower severity of overall injuries (NISS) observed in our study may be explained by the fact that the indication to transfer is clearer with severe single‐system injury than nonneurological multisystem trauma.…”
Section: Discussionmentioning
confidence: 54%
“…A similar rule for pediatric patients has been developed by the Pediatric Emergency Care Applied Research Network, although further research may define when MRI instead of CT may be indicated . Studies regarding CT head in the elderly, particularly with very minor trauma in the presence of different anticoagulants, may be warranted …”
Section: Resultsmentioning
confidence: 99%
“…Radiologists play an important role in the evaluation of geriatric patients as clinical evaluation of these patients becomes increasingly difficult because of overall frailty, comorbidities, and medication effects. 88 Because these patients have an increased number of illnesses and use the health care system more frequently, such as increased primary care visits, emergency visits, and hospitalizations, 89 it is inevitable that their own doctors will ask for more imaging studies.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%